A Possibilistic Simulation Model for Multiplayer Game Scenarios Using CPN Tools - Barreto, Franciny M.; Julia, Stéphane (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
In a multiplayer game scenario, the actions of a player most often have a direct influence on the actions of other players. Thus, the flow of the game can be changed causing an uncertainty behavior. This paper presents a method for modeling multiplayer video game scenarios based on a particular kind of Petri net, called WorkFlow net possibilistic. The constructors of the Possibility WorkFlow nets allow to represent the logical sequences of the actions of a game scenario, as well as the uncertainty behavior generated from the possible interactions between the players. The simulation of the model implemented in the CPN Tools tool allows to show through a gameplay graph the influence of the number of players in the effective participation of each player in the various activities proposed in the game. To illustrate the proposed approach, the game Tom Clancy's Ghost Recon: Wildlands is used.